The risk factors, pathogenesis and treatment of premature ovarian insufficiency - Yanjing Huang; Zhuo Liu; Yuli Geng; Fan Li; Runan Hu; Yufan Song; Mingmin Zhang; Kunkun Song (Journal of Ovarian Research)
Abstract Premature ovarian insufficiency (POI) is a prevalent condition that impacts female reproductive health and overall well-being. It is characterized by ovarian dysfunction, estrogen deficiency, and increased gonadotropin levels in women under 40 years old. The exact etiology and pathogenesis of POI remain incompletely understood, posing significant challenges for its treatment and prevention. This review article examines the pathogenic factors and mechanisms involved in POI, with a particular focus on the impact of environmental toxicants such as atmospheric particulate matter, endocrine-disrupting chemicals, pesticides, microplastics, heavy metals, and cigarette smoke on the development of POI. Furthermore, the treatments for POI are outlined, encompassing hormone replacement therapy, stem cell and exosome therapy, melatonin therapy, traditional Chinese medicine, in vitro activation, platelet-rich plasma therapy, and ovarian tissue cryopreservation. The primary objective is to raise awareness about the potential detrimental effects of environmental toxicant exposure on ovarian function and reserve, urging individuals to minimize their exposure to harmful substances and advocate for environmental protection. This review also aims to serve as a valuable resource for the prevention and management of POI.